Organic farming in the vicinity of conventional arable crops: which impact on revenues and costs?. (24th October 2019) - Bellassen, Valentin; Martin, Elsa; Villaverde, Ludivine
The neighbouring effect of organic fields on revenues and costs of conventional arable crop farms is tested. For this, a standard econometric model is applied to fine resolution economic and pedo-climatic data in the Deux-Sèvres department in Western France. The impact of the vicinity to organic farms on production is small but significant and negative. This may either be explained by a slightly higher infestation rate or by a remnant of correlation between organic field location and poor soil quality uncontrolled for by the pedo-climatic data. In any case, a high positive impact of the vicinity to organic fields mediated by crop auxiliaries is unlikely in this region. There is no impact of the vicinity to organic farms on crop protection costs. This could be explained by a routine behaviour of conventional farmers regarding crop protection or by social interactions between organic and conventional neighbours.